Measuring strangeness matrix elements of the nucleon - Henley, E. M.; Krein, G.; Pollock, S. J.; Williams, A. G. (Elsevier, 1991)
Experiments are proposed to measure various strangeness matrix elements of the nucleon. Examples are electro- and neutrino-production of φ mesons and the difference between neutrino and antineutrino scattering from isospin zero targets, e.g., deuterons. © 1991.